Penggunaan Strategi Story Impressions untuk Mengembangkan Kemampuan Analisis Teks Cerita Fantasi Pada Siswa SMP - Marlinda, Marlinda (Jurnal Profesi Pendidikan, 2023)
This study aims to understand the use of Story Impression strategies in an effort to develop the ability to analyze fantasy story texts in students of SMP Negeri 1 Tebo Regency. In this study, Pre-experiment design with one group pretest-postest design was used. The participants in this study were 5 students from class VII at SMP Negeri 1 Tebo. The measurement was conducted by utilizing a written description test developed together with several Indonesian language teachers who also served at SMP Negeri 1 Tebo. From the results of data processing that has been done, it is known that there is a change in the average score of the pretest which previously had a value of 62.4 then increased to 93.2 in the posttest. The change value is then described through N-Gain of 0.81. The N-Gain value is classified as a high change value. Based on this, it can be understood that the use of the Story Impression strategy is known to have benefits for developing the ability to analyze fantasy story text in groups.